INSTRUMEN TES HIGHER ORDER THINKING SKILL PADA MATERI KIMIA SMA - Etrie Jayanti (Chemistry Education Department of Education and Teaching Faculty, 2020)
Abstract: According to demands of curriculum 2013, assessment carried out on school should have led to increasing of higher order thinking skill. The lack of availability of questions are specifically designed to develop student’s higher order thinking skill causes students are not really proficient in solving higher order thinking skill questions. This study was research and development research purposing to determine development steps and quality of higher order thinking skill test instrument in one of high schools chemistry topic, i.e. colloid. The process of developing a higher order thinking skill test instrument used a formative research designed by Tessmer through 4 stages, namely: preliminary, self-evaluation, prototyping (expert reviews, one-to-one and small group) and field test. The data were obtained from the results of filling out validation sheets by expert reviews, questionnaires filled out by students, and test/trial of higher order thinking skill test instrument on students. The results of the development were categorically valid logically and empirically. The reliability of the test instrument was 0,65 with the high category. The item’s difficulty level was in the medium category. Six questions had good distinguishing power and one question had enough distinguishing power. The higher order thinking skill of students were in excellent, good, adequate, lacking and very poor categories respectively: 15,14%; 12,12%; 42,42%; 24,24%; 6,06%.